Raw Multi-Channel Seismic Shot Data from the Bermuda Rise, western North Atlantic acquired during the R/V Maurice Ewing expedition EW0106 (2001) (IEDA: Marine-Geo Digital Library, 2014)
This data set was acquired with a Multi-Channel Seismic system during Maurice Ewing expedition EW0106 conducted in 2001 (Chief Scientist: Dr. Dan Lizarralde; Investigator(s): Dr. James Gaherty and Dr. Dan Lizarralde). These data files are of SEGY format and include Multi-Channel Seismic Reflection shot data that have not been processed. Data were acquired as part of the project(s): Oceanic Upper Mantle Structure from Very Large Offset Seismic Refraction Experiments, and funding was provided by NSF grant(s): OCE00-02417. This data was cited by Lizarralde et al., 2004 and Gaherty et al., 2004.